REVIEW:The Characteristics of Genetic Resource of Bali Cattle (Bos-bibos banteng) and the Alternative of It's Conservation Methods - ACHMAD NUR CHAMDI (Society for Indonesian Biodiversity, 2005)
Bali cattle is an Indonesian native beef cattle, the result of domestication of Banteng (Bos-bibos banteng). The main problem faced in the development of Bali cattle is the low quality of breed, which is predicted as the effect of inbreeding or raising management. The affects of genetic and cross breeding which usually inflict a loss are the decreasing of cattle’s endurance, fertility and birth weight. Seeing the fact, the government effort to introduce a quality bull to the breed source areas, the determination of cattle release including the controll on the cutting of productive female cattle, and to exactly count the number of Bali cattle which can be released in order to do not disturb its population balance, so it is necessary to do conservation attempt by in-situ and ex-situ. The result of this study shows that the characteristics on genetic resource of Bali cattle which comprises documentation, evaluation on reproduction and production, and attempt in increasing Bali cattle’s genetic quality in Indonesia have been done, eventhough those are still limited.© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: Bali cattle, animal genetic resource, reproduction, production